PROBLEMATYKA ROZWODÓW W ŚWIETLE WYPOWIEDZI DUCHOWNYCH KATOLICKICH UCZESTNICZĄCYCH W BADANIU SOCJOLOGICZNYM - Stojanowska, Wanda; Kosek, Mirosław (Zeszyty Prawnicze, 2016)
DIVORCE ISSUES IN THE LIGHT OF THE RESPONSES OF PRIESTS PARTICIPATING IN A SOCIOLOGICAL SURVEY Summary The subject of this essay is a sociological survey on divorce conducted among 201 Roman Catholic priests. The survey was part of a larger project involving a wide range of interviewees including divorced persons. It was carried out in 2005-2006 using funds assigned for the statutory purposes of the Maria Grzegorzewska Academy of Special Education in Warsaw. The project was directed by Prof. W. Stojanowska, and Father M. Kosek PhD acted as a consultant for the compilation of the priests’ survey. The priests who participated in the survey came from all the voivodships in Poland. They answered a number of questions on issues such as the reasons behind conflicts between spouses and their (viz. the priests’) role in efforts to resolve them, and their legal awareness of issues associated with the divorce court’s determination of the cause of marital breakdown. Survey questions related particularly to alcoholism, infidelity, and a child’s disability as causes of the conflict. In the final part of the essay there are a few remarks summarising the results of the survey, showing that the priests who took part in it had a vast knowledge on marital conflict. The survey also showed that priests enjoy a considerable amount of trust and can be of substantial assistance as counsellors to spouses in conflict. The priests identified particular stages of conflict and difficulties in resolving them, which indicates that they had studied these problems in detail. The research results lead to one general remark: spouses need counselling to resolve their conflict and they look for assistance (however, sometimes at too late a stage). Also thanks to their availability, priests constitute one of the few professions that may provide spouses with such counselling.